Calreticulin del52 and ins5 knock-in mice recapitulate different myeloproliferative phenotypes observed in patients with MPN - Camélia Benlabiod (Nature Portfolio, 2020)
Calreticulin del52 and ins5 mutations induce two phenotypically distinct myeloproliferative neoplasms in patients. Here the authors show that modeling these mutations in knock-in mice recapitulate the two diseases and highlight how they impact the different hematopoietic compartments.